Specific Immune Response Kinetics and Mortality Patterns of Tilapia Oreochromis niloticus on Post-Cocktail Vaccination Period against the Infection of Aeromonas hydrophila and Streptococcus agalactiae - Sukenda Sukenda; Tuti Sumiati; Sri Nuryati; Angela Mariana Lusiastuti; Dendi Hidayatullah (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2017)
Fish vaccination aims to induce a specific immune response indicated by an increase of antibodies in vaccinated fish. However, in accordance with time the presence of will continue to decline. The purpose of this study was to determine the kinetics of specifik immune response and trend mortality against Aeromonas hydrophila and Streptococcus agalactiae on tilapia following vaccination with cocktail vaccine. Fish vaccinated through immersion for 30 minutes in a solution of diluted vaccine. Challenge test was performed for three periods, on day 22, 50, and 78 post-vaccination, fish were challenged with single infection of A. hydrophila 108 cfu. mL-1 and S. agalactiae 104 cfu. mL-1 and co-infection of both bacteria by intraperitoneal. During rearing, the blood fish were taken for determining of serum antibodies, and its measured by ELISA. The results showed that the concentration of specific antibodies vaccinated fish were significantly higher than the control. The basal antibody levels of A. hydrophila before vaccination were higher than S. agalactiae with OD of 0.104 and 0.069 respectively. The maximum antibody response was reached within 70 days of the A. hydrophila OD= 0.264 and 56 days against S. agalactiae OD= 0.188. The mortality rate in the control group was significantly higher than vaccinated on all types and each challenge test period. The trend of mortality due to a single infection of A. hydrophila and co-infections occur more quickly than by S. agalactiae. Lowest mortality occurred in the vaccinated group at 50 day tested challenge.Keywords: kinetics antibody, Aeromnas hydrophila, Streptococcus agalactiae, Oreochromis niloticus